AKTUALISASI PENDIDIKAN ISLAM DALAM PENGELOLAAN LINGKUNGAN HIDUP: Studi Relasi Antara Pendidikan Islam dan Budaya Mistis Dalam Pelestarian Lingkungan - Dedi Wahyudi; Siti Aisah (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
This study aims to describe the relationship between Islamic Education and Mystical Culture in Environmental Conservation. This research is a study of literature by collecting the same source as much as possible. There is much research relevant to this journal article. From the analysis of the various studies, the result of this research is the relationship between Islamic education and mystical culture in the preservation of the environment that is the positive side and the negative side. The positive side is that with the existence of a mystical culture that exists in society makes society not arbitrary to nature, people who embrace and believe in the mystical is more polite, more careful when doing or connect with nature. While the negative side of the community that embraces or believes in the existence of this mystical tend to put forward and glorify the culture compared with Islam that dianutnya